2023
DOI: 10.1007/s00018-023-04706-x
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial BCKD complex interacts with hepatic apolipoprotein E in cultured cells in vitro and mouse livers in vivo

Abstract: Background and aims Apolipoprotein E (APOE) is known for its role in lipid metabolism and its association with age-related disease pathology. The aim of the present work was to identify previously unknown functions of APOE based on the detection of novel APOE protein–protein interaction candidates. Approach and results APOE targeted replacement mice and transfected cultured hepatocytes expressing the human isoforms APOE3 and APOE4 were used. For 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…( E ), the circulating APOE concentration was determined in the plasma of 4 h fasted mice after termination of the feeding trial using an ELISA kit. Hepatic APOE protein levels were analyzed by Western blotting and the data shown are according to Rueter et al [ 57 ]. Relative mRNA levels of human APOE were analyzed in the liver (squares) and visceral adipose tissue (circles) by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( E ), the circulating APOE concentration was determined in the plasma of 4 h fasted mice after termination of the feeding trial using an ELISA kit. Hepatic APOE protein levels were analyzed by Western blotting and the data shown are according to Rueter et al [ 57 ]. Relative mRNA levels of human APOE were analyzed in the liver (squares) and visceral adipose tissue (circles) by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…The study was performed according to the German regulations of animal welfare and approved by the local animal ethical committee. The mouse experiment has been described also elsewhere [ 55 - 57 ]. In brief, twelve male APOE3 and APOE4 targeted replacement (six per APOE genotype group) and six unmodified C57Bl/ 6JBOM mice were purchased from Taconic Europe A/S (Ry, Denmark).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCKDHA and VDAC1 are both mitochondrial proteins that jointly participate in lipid metabolism processes. Research has indicated that BCKDHA and VDAC1 can undergo immunoprecipitation with APOE in mouse liver extracts ( 32 ). This interaction plays a crucial role in the energy production processes of mitochondria and helps the liver to adapt to its energy demands.…”
Section: Discussionmentioning
confidence: 99%